2012
DOI: 10.5194/isprsarchives-xxxviii-4-w19-203-2011
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Based 3d Scanning vs. Laser Scanning – Competitive Data Acquisition Methods for Digital Terrain Modelling of Steep Mountain Slopes

Abstract: ABSTRACT:The paper presents how terrestrial laser scanning (TLS) and terrestrial digital photogrammetry were used to create a 3D model of a steep mountain wall. Terrestrial methods of data acquisition are the most suitable for such relief, as the most effective registration is perpendicular to the surface. First, various aspects of photo-based scanning and laser scanning were discussed. The general overview of both technologies was followed by the description of a case study of the western wall of the Kościele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Even though the accuracy of photogrammetric methods can be increased by using high-resolution camera sensors and decreasing the distance from the surface to be monitored, the results will never be comparable to the accuracy of other methods, such as laser scanner surveys (Kolecka, 2011). However, millimetric or centimetric displacement measurements are typically unnecessary for many landslides, and long-term or high frequency monitoring could be more important, especially for large and intermittent movements.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
See 1 more Smart Citation
“…Even though the accuracy of photogrammetric methods can be increased by using high-resolution camera sensors and decreasing the distance from the surface to be monitored, the results will never be comparable to the accuracy of other methods, such as laser scanner surveys (Kolecka, 2011). However, millimetric or centimetric displacement measurements are typically unnecessary for many landslides, and long-term or high frequency monitoring could be more important, especially for large and intermittent movements.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…The use of images from different points of view in terrestrial digital photogrammetry was shown to be a promising technique to obtain 3D reconstructions of slope surfaces (Kolecka, 2011;Westoby et al, 2012). In the future, this tool will likely be a valuable way to obtain accurate metric 3D displacement fields, as has already been demonstrated for laboratory applications (Szeliski and Kang, 1994;Pons et al, 2007) and aerial photos (Kaab, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Obtained stereo pair images are processed in PhotoModeler Scanner software, which derives accurate, high quality 3D models and enables measurements based on photographs. The process is known as photo-based 3D scanning [29] or image-based modelling [30] and is used for producing a dense point cloud (Dense Surface Modelling) from images of textured surfaces. The multi-sheet camera calibration is executed before the automatic Dense Surface Modelling.…”
Section: Soil Surface Roughness and Surface Changesmentioning
confidence: 99%
“…Furthermore, integration of geophysical sensors such as geophones, seismographs and accelerometers for efficient rockfall monitoring has been proposed in [5,6]. Besides these techniques, image based methods that rely upon the construction of accurate digital elevation models from stereo photographs have been proposed, evaluated and implemented in several studies [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%